2021
DOI: 10.21203/rs.3.rs-809824/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence of Accelerated Epigenetic Aging of Breast Tissues In Patients With Breast Cancer Is Driven By CpGs Associated With Polycomb Related Genes

Abstract: Purpose: Age is one of the strongest risk factors for the development of breast cancer, however the underlying etiology linking age and breast cancer remains unclear. We have previously observed links between epigenetic aging signatures in breast/tumor tissue and breast cancer risk/prevalence. However, these DNA methylation-based aging biomarkers capture diverse epigenetic phenomena and it is not known to what degree they relate to breast cancer risk, and/or progression. Methods: Using six epigenetic clocks, w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Further experiments are needed to examine the direction and causality of this effect. Previous studies in humans and other mammalian species have shown that target sites of PRC2 gain methylation with age 23,2530 , although this was identified as an enrichment among a small number of CpGs rather than a global survey of PRC2 targets. Two different biological processes have previously been suggested to contribute to the age-dependent gain of DNAm within PRC2 LMRs.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Further experiments are needed to examine the direction and causality of this effect. Previous studies in humans and other mammalian species have shown that target sites of PRC2 gain methylation with age 23,2530 , although this was identified as an enrichment among a small number of CpGs rather than a global survey of PRC2 targets. Two different biological processes have previously been suggested to contribute to the age-dependent gain of DNAm within PRC2 LMRs.…”
Section: Discussionmentioning
confidence: 81%
“…These regions are also enriched in ageassociated hypermethylation in cancer 23 and in normal adults 24 . While previous studies have identified the enrichment of PRC2 targets within the age-dependent methylome 23,[25][26][27][28][29][30] , they are mainly based on a selected number of CpG sites or a small number of samples. In addition, the commonly used microarray assays in previous studies only cover a small fraction of all CpGs genome-wide (1-3 percent of all CpGs in Illumina BeadChip arrays, Illumina.com 2022).…”
Section: Introductionmentioning
confidence: 99%
“…(D) Differences in CellDRIFT epigenetic risk in healthy breast tissue of known breast cancer patients and participants with no history of prior breast cancer (Rozenblit et. al 2022) [37]. DNAmAge scores were residualized by age prior to analysis.…”
Section: Resultsmentioning
confidence: 99%
“…All data used in this study is summarized below: Training : hTERT training data (this study, n=31 samples), Validation : hTERT validation data (this study, n=14), Liver aging (GSE48325), Brain aging (GSE74193), Blood aging (GSE40279), Skin aging (GSE52980), Primary Astrocytes (this study, n=25), Fetal Astrocytes (this study/GSE202554), Primary Dermal Fibroblast and Primary Mammary Fibroblasts (E-MTAB-8327), Cancer : Pooled cancer samples (GSE53051), Breast cancer survival data (GSE37754), Healthy breast tissue - Rozenblit et. al 2022 [37], Whole-body tissue (ENTEx study), Reprogramming : Yamanaka fibroblast re-programming and passaging data (GSE54848) and iPSC/ESC passaging data (GSE31848).…”
Section: Methodsmentioning
confidence: 99%
“…With regards to the alterations—acceleration or deceleration—observed in the clocks, various associations have been investigated, particularly the aforementioned links with environmental factors and disease (Fransquet et al, 2019; Levine et al, 2018; Lu et al, 2019; Marioni et al, 2015; Oblak et al, 2021), to ascertain whether the DNAm alterations which occur during these processes could drive the changes observed in the clocks. For instance, a recent study investigating DNAm age acceleration in the non‐tumoral breast tissue of breast cancer patients demonstrated that the observed alteration in the epigenetic clock could be explained by a subset of the clock CpGs that suffer from the well‐known cancer‐associated hypermethylation of Polycomb associated loci (Rozenblit et al, 2022). Indeed, clocks have been constructed which partly reflect the DNAm alterations induced by cancer‐related lifestyle factors such as smoking (Lu et al, 2019).…”
Section: Dna Methylation Clocks As New Tools In the Study Of Diseasementioning
confidence: 99%